State University of Land Use Planning - a driver of ecological development of small regions in the conditions of Covid-19 - Yuliya, Yurova; Vera, Shirokova; Roy, Shirokov; Pavel, Lepekhin; Alla, Khutorova (Universitas Diponegoro, 2022)
Responding to global global challenges and sustainable development goals, the State University of Land Use Planning (LUP) is trying to modernize its scientific, educational and economic activities and introduce the best available technologies in the field of rational nature management. The University pursues an environmental policy, which should become a guarantor of sustainable environmentally oriented development of small regions in accordance with the SDG.Since 2018, LUP has been actively participating in events organized by the IU Green Metric community. The use of the